The acoustic orchestrations - Scriabin, Aleksandr Nikolayevich 1872-1915; Sibelius, Jean (EU Sony Classical)
Disc: 1 1. Piano Sonata No. 5 in F-Sharp, Op. 53 2. Deux Morceaux, Op. 57; No. 1, Desir 3. Deux Morceaux, Op. 57; No. 2, Caresse dansee 4. Sonatina for Piano in F-Sharp Minor, Op. 67 No. 1; I. Allegro 5. Sonatina for Piano in F-Sharp Minor, Op. 67 No. 1; II. Largo 6. Sonatina for Piano in F-Sharp Minor, Op. 67 No. 1; III. Allegro Moderato 7. Sonatina for Piano in E, Op. 67 No. 2; I. Allegro 8. Sonatina for Piano in E, Op. 67 No. 2; II. Andantino 9. Sonatina for Piano in E, Op. 67 No. 2; III. Allegro 10. Sonatina for Piano in B-Flat Minor, Op. 67 No. 3; I. Andante 11. Sonatina for Piano in B-Flat Minor, Op. 67 No. 3; II. Andante - Allegretto 12. 3 Lyric Pieces for Piano, Op. 41, "Kyllikki"; I. Largamente - Allegro 13. 3 Lyric Pieces for Piano, Op. 41, "Kyllikki"; II. Andantino 14. 3 Lyric Pieces for Piano, Op. 41, "Kyllikki"; III. Commodo - Tranquillo Disc: 2 1. Piano Sonata No. 5 in F-Sharp, Op. 53 2. Piano Sonata No. 5 in F-Sharp, Op. 53 (Mike Rank 1) 3. Piano Sonata No. 5 in F-Sharp, Op. 53 (Mike Rank 2) 4. Piano Sonata No. 5 in F-Sharp, Op. 53 (Mike Rank 3) 5. Piano Sonata No. 5 in F-Sharp, Op. 53 (Mike Rank 4)